Removal of Ethyl Violet Dye from Aqueous Solution by Graphite Dust and Nano Graphene Oxide Synthesized from Graphite Dust (Communication In Physical Sciences, 2019)
Communication in Physical Sciences 2019. 4(2): 103-109Author: Anduang Ofuo Odiongenyi Nano graphene oxide was synthesized from graphite dust using Hummer’s method. The graphite dust and the synthesized nano graphene oxide were used as an adsorbent to remove ethyl violet dye from aqueous solution. The equilibrium amount of dye adsorbed by graphite dust at 303, 313, 323 and 333 K ranged from 5.303 to 37.236, 1.551 to 22.779, 1.058 to 26.026 and from 1.298 to 22.849 mg/g respectively. For nano graphene dust, the equilibrium amount ranged from 1.904 to 41.467, 1.834 to 55.712, 1.058 to 26.023 and from 1.298 to 22.849 mg/g at 303, 313, 323 and 333 K respectively. Nano graphene oxide exhibited better performance than graphite dust except at 333 K. The adsorption of ethyl violet occurred through a physical adsorption mechanism at 303 K but at higher temperature, chemisorption dominated, Langmuir isotherm best described the adsorption of the dye. The theoretical adsorption capacity of theadsorbent increased with temperature. Nano graphene oxide displayed better surface modification properties than graphite dust.